Hemodynamic and gas exchange effects of inhaled iloprost in patients with COPD and pulmonary hypertension - Wang, Lan (Int J Chron Obstruct Pulmon Dis, 2017)
Studies have shown that vasodilators such as iloprost can be useful for treating pulmonary hypertension (PH). However, in patients with COPD, vasodilators may inhibit hypoxic pulmonary vasoconstriction and impair gas exchange. The efficacy and safety of iloprost inhalation was assessed in 67 patients with PH associated with COPD (COPD-PH), diagnosed by right heart catheterization. Of these, 37 patients had severe PH (mean pulmonary arterial pressure [mPAP] >35 mmHg or mPAP 25–35 mmHg with low cardiac index [<2.0 L⋅min(−1)⋅m(−2)]). All patients received a single 20 µg dose of iloprost via a nebulizer (4.4 µg delivered at the mouthpiece). No serious adverse events were reported. Hemodynamic and gas exchange parameters (arterial blood gas and shunt fraction [Qs/Qt]) were measured or calculated at baseline and 10 min after iloprost inhalation. mPAP decreased by 2.1 mmHg (95% CI, −3.3 to −1.0), pulmonary vascular resistance (PVR) decreased by 62.4 dyn⋅s⋅cm(−5) (95% CI, −92.9 to −31.8), and cardiac output increased by 0.4 L⋅min(−1) (95% CI, 0.2–0.5). There was a more significant decline in PVR in patients with severe COPD-PH than in those with nonsevere COPD-PH. Hypoxemia and intrapulmonary shunt were more extreme in patients with severe COPD-PH. However, there were no significant differences in arterial blood gas and Qs/Qt between patients with nonsevere and severe forms of COPD-PH. In conclusion, iloprost improved pulmonary hemodynamics without detrimental effects on arterial oxygenation in patients with COPD-PH, even in those with severe PH. These findings suggest that the short-term use of iloprost in patients with COPD-PH is effective and well tolerated.